From paper to podium: Quantifying the translational potential of performance nutrition research - Close, G. L.; Kasper, A. M.; Morton, J. P. (Sports Medicine, 2019)
Sport nutrition is one of the fastest growing and evolving disciplines of sport and exercise science, demonstrated by a 4-fold increase in the number of research papers between 2012 and 2018. Indeed, the scope of contemporary nutrition-related research could range from discovery of novel nutrient-sensitive cell-signalling pathways to the assessment of the effects of sports drinks on exercise performance. For the sport nutrition practitioner, the goal is to translate innovations in research to develop and administer practical interventions that contribute to the delivery of winning performances. Accordingly, step one in the translation of research to practice should always be a well-structured critique of the translational potential of the existing scientific evidence. To this end, we present an operational framework (the "Paper-2-Podium Matrix") that provides a checklist of criteria for which to prompt the critical evaluation of performance nutrition-related research papers. In considering the (1) research context, (2) participant characteristics, (3) research design, (4) dietary and exercise controls, (5) validity and reliability of exercise performance tests, (6) data analytics, (7) feasibility of application, (8) risk/reward and (9) timing of the intervention, we aimed to provide a time-efficient framework to aid practitioners in their scientific appraisal of research. Ultimately, it is the combination of boldness of reform (i.e. innovations in research) and quality of execution (i.e. ease of administration of practical solutions) that is most likely to deliver the transition from paper to podium.